2022
DOI: 10.1037/pspp0000416
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the belief system of a person.

Abstract: Theories of belief system structure and dynamics assume that belief systems are a person-level construct. However, measures of belief system structure do not measure the structure of person-level belief systems and instead measure aggregated belief system structure (e.g., the belief system in a particular country). In this paper, I show that a measure of conceptual similarity between attitudes and identities of a belief system works as a valid, reliable, flexible, and efficient measure of person-level belief s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Our comparisons of people according to their self-classification of ideology, which are methodologically similar to previous comparisons between high and low information voters Fishman & Davis, 2022), assume that the three networks are representative of the belief networks of the individuals within those groups. Other techniques, for example comparisons of the way that individuals within each group rate the conceptual similarity between target political constructs (Brandt, 2022), may have utility in future studies designed to verify the observed differences at the level of individuals. Hence, for example, we would expect people who self-classify on the Left or Right to rate policies as more conceptually similar than those who self-classify as belonging to the Center.…”
Section: Discussionmentioning
confidence: 99%
“…Our comparisons of people according to their self-classification of ideology, which are methodologically similar to previous comparisons between high and low information voters Fishman & Davis, 2022), assume that the three networks are representative of the belief networks of the individuals within those groups. Other techniques, for example comparisons of the way that individuals within each group rate the conceptual similarity between target political constructs (Brandt, 2022), may have utility in future studies designed to verify the observed differences at the level of individuals. Hence, for example, we would expect people who self-classify on the Left or Right to rate policies as more conceptually similar than those who self-classify as belonging to the Center.…”
Section: Discussionmentioning
confidence: 99%
“…First, although the first experiments used an accepted method for estimating belief system structure, the method estimates the belief system at the sample level and may not appropriately identify the most central and peripheral nodes for each participant (Brandt & Morgan, 2022). Therefore, in this study, belief systems of individuals were estimated using a conceptual similarity task, which has been shown to be a valid measure of a person's belief system (Brandt, 2022; see also Judd et al., 1991). This allows us to identify the most central and peripheral attitudes in each participant's belief system at the pretest and assign them to central and peripheral conditions that are tailored to each participant's belief system structure.…”
Section: Methodsmentioning
confidence: 99%
“…That said, as we detail in our supplemental materials, we do not have much evidence that the manipulations affected the moral conviction of the attitudes in our study. One additional way to try and capture this idea would be to test if moral reframing messages create new connections in the belief system (e.g., with the relevant moral values) using the conceptual similarity task as an outcome variable (e.g., Brandt, 2022).…”
Section: Interpretation 1: Theoretical Limitationsmentioning
confidence: 99%
See 2 more Smart Citations